Analysis of Ca(II) and Cd(II) Binding to the C-Domain of Human Cardiac Troponin C using Intrinsic Fluorescence Spectroscopy - Sengelmann, Rudy A. (My University, 2024)
Heavy metal toxicity has been a health concern for many years; however, the mechanisms that these metals use to impart their toxicity remain unclear. Cadmium (Cd), a toxic metal, has been discovered to mimic calcium (Ca), an essential metal, due to the similarity in ionic radii and charge. This research focuses on understanding the impact of cadmium binding to human cardiac troponin C, a cardiac muscle protein that binds calcium to promote heart muscle contraction. This protein contains an EF-hand motif, which the helix-loop-helix structure can characterize. It is composed of the N terminal domain (NTD), which contains two EF-hand motifs where only one binds a divalent calcium ion, Ca(II), and the C terminal domain (CTD), which contains two EF-hands, each binding a Ca(II) ion. The overarching goal of this project is to express and purify the CTD so that the interactions of Ca(II) and Cd(II) in this domain can be studied. To do this, the protein was optimized in pLysS cells with an N-terminus His-tag for easy purification. Through earlier research, the full-length protein was purified using a Phenyl Sepharose column and cleaved into the NTD and CTD at the TEV cleavage site between the two domains. This was then purified using a nickel column, binding to the His-tagged NTD and uncleaved full-length protein, further purifying and isolating the CTD. Once isolated, intrinsic fluorescence spectroscopy was used to study the interactions and mimicry of cadmium to the C terminal domain of calcium-binding human cardiac troponin C. Through further research, there may be a more fundamental understanding of how this mimicry may influence cardiovascular disease and cognitive development concerns.
Keywords: Calcium; Cadmium; hcTnC; Fluorescence